PENGARUH DAYA TARIK WISATA DAN FASILITAS LAYANAN TERHADAP KEPUASAN WISATAWAN (WISATA TANJUNG PEJUANG DESA TUADA) - Friskila Hallo; Ida Hidayanti; Ibnu Sina Hi. Yusuf (Jurnal Manajemen Sinergi, 2021)
ABSTRACTObjective: This research purposed to identify the influence of Attraction and Service Facilities on Tourist Satisfaction in Tajung Pejuang Desa Tuada Beach. This research type is an explanatory research with quantitative approach. Data were collected by using questionnaires distributed to the 100 tourists who have visited to Tanjun Pejuang Desa Tuada Beach by simple random sampling technique.Methodology: Data analysis are used consist of descriptive analysis, classic assumption test, multiple linier regression analysis, F test and t test. Finding: H1 and H2 accepted at the 5% 10% confidence level.Conclusion: The result of this study showed that Attraction and Service Facilities simultanously have a significant effect on Tourist Satisfaction, AttractionÂ  has a significant effect on Tourist Satisfaction, and Service Facilities has a significant effect on Tourist Satisfaction. Â